Cambios recientes en los patrones migratorios a la Zona Metropolitana de la Ciudad de México, ZMCM - Corona Cuapio, Reina; Luque González, José Rodolfo (El Colegio de México A.C., 1992)
This study analyzes the magnitude, evolution over time, and place of origin of migrants to the ZMCM during the 1970's and 80's. More specifically, the study attempts to test the following hypothesis: attraction of migrants to the ZMCM has diminished over time; by comparison, it has grown in medium sized cities; thus the ZMCM is emerging as an important origin of migrants toward other cities. The article also provides an analysis of the changes in the characteristics of the migrants such as gender, age, schooling, rural or urban origins, etcétera.